Intensidade e duração dos esforços físicos em aulas de Educação Física curriculares - Kremer, Marina Marques (2010)
The school, and in particular the Physical Education classes (PE), are in a privileged position for the promotion of health among children and adolescents. However, little is known about the PE programs in Brazil. The aim of this study was to estimate the intensity and duration of physical efforts in PE classes in primary and secondary school. Methodology: A school-based cross-sectional study was carried out. A multistage sampling strategy was used, including stratification by education network (public and private) and grade. We sampled 16 schools, and 272 students took part in the study, totaling 218 classes observations. We administered a questionnaire to identify physical spaces and materials available to the PE classes and a questionnaire for students. The outcome variables were evaluated by an instrument of direct observation the System for Observing Fitness Instruction Time SOFIT; and the intensity of the classes was measured by accelerometry. To determine the intensity of the efforts we used the following cut-off points (in counts): sedentary activities (0-100), light activities (101-2000), moderate activities (2001-4999), vigorous (5000-7999) and very vigorous (>8000). The outcome "moderate to vigorous physical activity (MVPA)" was created by grouping moderate, vigorous and very vigorous activities. Results: The mean duration of the classes was 35.6 minutes (SD 6.0), whereas the mean time spent in MVPA was 12.3 minutes (SD 9.7). The mean proportion of the time spent on MVPA was 32.7% (SD 25.2). Boys (44.1%) spent a higher proportion of the classes in MVPA as compared to girls (21.0%; p<0.01). Students who practice physical activity outside the PE classes were more likely to engage in MVPA during the classes. There were no significant differences in the practice of MVPA in different educational networks and school grades. Conclusions: The proportion of time spent in MVPA was low, indicating that during PE classes students are, most of the time, carrying out activities that are not of sufficient intensity and duration to produce organic changes leading to health benefits. Urgent strategies are needed in order to increase the intensity and duration of physical efforts in Physical Education classes